JARGON DALAM INTERAKSI SOSIAL BAHASA SASAK OLEH SISWA MAN LOMBOK BARAT - Muhsan Muhsan (Cendekia: Jurnal Pendidikan dan Pembelajaran, 2017)
This research described the use of jargon in social interaction of Sasak language. The researcher evoked the issue on forms, function and meaning of jargon used by students of MAN Gerung, West Lombok regency.  This research is a descriptive research that used qualitative approach. The techniques of data collection were observation and documentation. The data were analyzed through specific linguistic feature based on linguistic attitude. The results were summarized as follows: 1) forms of jargon were found in terms of word and phrase forms, 2) the functions of jargon were for communicative simplicity, identiying function and milieu restoration. While the meaning of the data jargon jargon MAN Gerung students varies based on the students' understanding.